Focal Therapy for Prostate Cancer: Evolutionary Parallels to Breast Cancer Treatment. Issue 1 (21st January 2023) - Labbate, Craig V.; Klotz, Laurence; Morrow, Monica; Cooperberg, Matthew; Esserman, Laura; Eggener, Scott E.
Abstract : Purpose: Our goal was to review the history of the adoption of focal therapy for breast and prostate cancer and review common barriers to implementation. Materials and Methods: A narrative review of the literature was performed of English-language MEDLINE indexed articles of breast-conservation therapy and prostate cancer focal therapy. Results: The introduction of focal therapy in breast cancer began with pioneering case series, and multiple randomized trials were performed prior to widespread adoption. Focal therapy for prostate cancer has just started the process of clinical trials with a single published randomized controlled trial. Commonly cited barriers to the adoption of prostate focal therapy include historical views of Halstedian tumor biology, tumor multifocality, over-detection, limitations in prostate imaging, and trial design end points. Conclusions: The adoption of breast-conserving therapy evolved over decades and used data from multiple large, randomized, clinical trials. Barriers to the adoption of prostate cancer local therapy are similar to those faced by breast cancer clinical trials. Completion of well-designed trials in prostate cancer focal therapy is essential for its evidence-based adoption.